Effects of silkworm fiber position on flexural and compressive properties of silk fiber-reinforced composites - Ariyani Faizah; Dendi Murdiyanto; Yulita Nur Widyawati; Narawidya Laksmi Dewi (Dental Journal (Majalah Kedokteran Gigi), 2018)
Background: Fiber-reinforced composites represent a combination of fiber-reinforced composite materials. The availability of fiber within dentistry in Indonesia is limited and, therefore, requires lengthy advance ordering. The increasing use of fiber derived from natural materials, such as silk, is of greater concern due to its considerable mechanical strength, biocompatibility and wider availability. The application of fiber will increase the mechanical strength of fiber-reinforced composites, including both flexural and compression strength. One factor affecting the mechanical strength of fiber is the laying of fiber or fiber position. Purpose: The purpose of this research is to establish the influence of silkworm fiber position on both the flexural and compression strength of silk fiber-reinforced composites. Methods: Flexural strength and compression strength tests using a universal testing machine involved the division of the research population into three treatment groups: compression side, neutral side and tension side. Results: The results of data analysis indicated that the tension side group possessed the highest flexural strength (121.42 MPa), while the compression side group demonstrated the highest compression strength (337.65 MPa). A one-way ANOVA analysis test produced a significant result of p = 0.000 (<0.05) both for silkworm fiber position effect and compression strength of silk fiber reinforced composites. Conclusion: The position of silkworm fiber will affect its flexural strength as well as that of the compression of silk fiber-reinforced composites.